The meaning of mergers and acquisitions in labor law (Journal of actual problems of jurisprudence, 2018)
This article examines a new term for the Kazakh companies called mergers and acquisitions. Many resources and managers say that mergers and acquisitions help to increase market efficiency by capturing the interaction between the firms. However, the seizures are also imposed on external factors (both positive and negative) on the other firms in different industries. This article describes a new concept of equilibrium, intended to explain and predict the absorption in this situation in the different sectors in Kazakhstan’s entities. As this article has shown the reorganization of our domestic and foreign enterprise. At the time of the mergers and acquisitions, studies show only the positive aspects for our country. Nevertheless, the experiment can be compared this term that does not only bring the benefits to all commercial entities. In this paper, we also consider that large enterprises in Kazakhstan in various sectors, such as: oil and gas, mining and financial sectors that showing big interest to this concept. This shows that our country can lift the economy through such reorganizations. Key words: mergers, acquisitions, reorganizations, commercial entities, foreign entities.